2005
DOI: 10.1554/04-419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Influences on the Germination of Arabidopsis Thaliana in the Field

Abstract: Seasonal germination timing strongly influences lifetime fitness and can affect the ability of plant populations to colonize and persist in new environments. To quantify the influence of seasonal environmental factors on germination and to test whether pleiotropy or close linkage are significant constraints on the evolution of germination in different seasonal conditions, we dispersed novel recombinant genotypes of Arabidopsis thaliana into two geographic locations. To decouple the photoperiod during seed matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
151
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 56 publications
6
151
3
Order By: Relevance
“…1A). Lower temperatures during seed set also increase progeny dormancy (6), but we observed no effect of photoperiod on dormancy either before or after flowering, as has been reported previously (7,8). Therefore, temperature signals before seed fertilization are remembered by the parent plant and used to control offspring behavior.…”
supporting
confidence: 71%
“…1A). Lower temperatures during seed set also increase progeny dormancy (6), but we observed no effect of photoperiod on dormancy either before or after flowering, as has been reported previously (7,8). Therefore, temperature signals before seed fertilization are remembered by the parent plant and used to control offspring behavior.…”
supporting
confidence: 71%
“…Arabidopsis thaliana, a highly selfing (Abbott and Gomes 1989) annual mustard, matures and disperses seeds in both spring and autumn in New England (see also Thompson 1994), and seasonal environmental factors influence germination timing. In companion papers, we documented highly plastic and genetically variable responses of germination timing to geographic location and season of seed dispersal (Donohue et al 2005a), and we showed that germination timing explained a large proportion of the variation in fitness among genotypes in some conditions but not others (Donohue et al 2005b). Here we examine indirect effects of germination timing on fitness operating through the phenotypic expression of postgermination characters and through natural selection on those postgermination characters.…”
mentioning
confidence: 73%
“…Seeds of Cal, were acquired through the Arabidopsis Biological Resource Center at Ohio State University (stock CS1062), and Tac seeds were collected by T. Mitchell-Olds. Please see Donohue et al (2005a) for details on the lines and their maintenance. …”
mentioning
confidence: 99%
“…Field studies have revealed multiple seasonal germination cohorts in many A. thaliana populations (26,45,46), as well as seasonal differences in natural selection on life history traits (47,48). Moreover, genotypes may differ in phenology and fitness across natural environments (48-51), which may promote reproductive isolation.…”
Section: Discussionmentioning
confidence: 99%